Precursor of hemangioma: the diagnosis is not always easy. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
At birth, the differential diagnosis between salmon patch, port-wine stain, hemangioma precursor and capillary malformation / arteriovenous malformation is important because it is necessary to pronounce on the regression or not of the lesions, on the possible investigations to do, on the prognosis and on the type of therapeutic approach. However, the diagnosis between these very different entities is not always easy. The most common mistake is to diagnose port-wine stain, to realize after a few days that it is instead a segmental hemangioma or a PHACE syndrome. The dermoscopic examination is not easy to perform in the newborn due to its continuous movement and is not always decisive (2); the presence of coarse and irregular telangiectasias (1) favors the diagnosis of hemangioma. In doubtful cases it is wise to wait a few days before communicating the definitive diagnosis.